2013
DOI: 10.1080/03610926.2011.621576
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Properties of the LS-estimator of a Gaussian Autoregressive Process by an Averaging Method

Abstract: This article deals with the problem of parameter estimation of a continuous-time p-dimensional Gaussian autoregressive process. In the stable case, we combine averaging and weighting methods to establish, for the weighted LS-estimator (least-squares estimator)˜ of , an almost-sure central limit theorem (ASCLT), a quadratic strong law (QSL) and a central limit theorem (CLT) associated to the QSL with arithmetic convergence rates. In the unstable case, we establish for the LS-estimatorˆ of , the same optimal asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Further, stationarity and ergodicity studies for affine diffusion processes found a particular interest by many authors, see, e.g., [4,10,18,19,25,26,27] and [43], where they give sufficient conditions for the existence of a unique stationary distribution and for the ergodic property. Moreover, several papers have studied the drift parameter estimation in different models, see, e.g., [2,3,5,6,7,9,15] and the references therein. It should be noted that statistical inferences of AD(1, n) model were not considered and more generally, inferences of affine multidimensional diffusions are rarely treated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, stationarity and ergodicity studies for affine diffusion processes found a particular interest by many authors, see, e.g., [4,10,18,19,25,26,27] and [43], where they give sufficient conditions for the existence of a unique stationary distribution and for the ergodic property. Moreover, several papers have studied the drift parameter estimation in different models, see, e.g., [2,3,5,6,7,9,15] and the references therein. It should be noted that statistical inferences of AD(1, n) model were not considered and more generally, inferences of affine multidimensional diffusions are rarely treated.…”
Section: Introductionmentioning
confidence: 99%